Knowledge transfer success - How to facilitate effective knowledge transfer to prevent recurring quality issues - Wall, Amelia; Lippel, Rebecca (My University, 2020)
Purpose: The purpose is to identify facilitators to effective knowledge transfer be- tween two departments within a manufacturing company, whereof one is responsible for solving quality issues and one is responsible for implementing the solution in new development projects. These facilitators contribute to achieving knowledge transfer success, in this case defined as the prevention of recurring quality issues. Research questions: To fulfil the purpose of the thesis, three research questions were answered: (1) What factors prevent an effective knowledge transfer process? (2) How does motivation and willingness affect knowledge sharing and transfer? (3) What are success factors to effective knowledge transfer? Method: The study was of qualitative nature, and involved a deep investigation of the current knowledge transfer process at a case company by conducting interviews with employees at two relevant departments. Interviews were also held with aca- demics to gain external insights on the subject. The research was complemented by extensive theoretical research, of which a large part of the analysis is based upon. Results: Barriers lifted in the theoretical framework, such as the level of knowledge articulability and embeddeddness, different types of distance barriers, organisational culture, prioritisation, and leadership were also found at the case company. Four ad- ditional barriers were identified from the case study, namely resource misallocation and time constraints, employee turnover, missing verification method, and unclear process description. With regards to motivation and willingness to transfer knowl- edge, these were also found to have a substantial impact in terms of external and interval motivators, attitude and pressure to transfer knowledge, and control over the transfer process. Lastly, a set of success factors to effective knowledge transfer were also identified. These include establishing efficient and frequent communication, a sense of community and a common goal, a sense of urgency and connection to the problem, and continuous transfer of knowledge to colleagues and the organisation. Conclusion: Having an organisational culture favouring knowledge transfer com- bined with a common purpose and goal, a connection to the issue, a sense of ur- gency, and frequent and efficient communication between teams are believed to be key factors to facilitate effective transfer and achieve knowledge transfer success. Furthermore, knowledge need to consistently be preserved within the organisation, provided resources need to be sufficient and aligned with requirements and stated knowledge transfer goals, and a clear description of the transfer process is required.
Keywords: knowledge transfer; knowledge sharing; quality in NPD; prevent recurring quality issues; barriers to knowledge transfer; successful knowledge transfer; effective knowledge transfer; willingness to share knowledge; motivation to transfer knowledge v